Peer recommendations on how to improve clinical research, and Conference wrap-up. Issue 1 (May 2013) - Chad, David A.; Rowland, Lewis P.; Armon, Carmel; Bedlack, Richard; Durham, Heather; Factor-Litvak, Pam; Heiman-Patterson, Terry; Heitzman, Daragh; Lacomis, David; Ludolph, Albert; Maragakis, Nicholas; Miller, Robert; et al.
Abstract To promote clinical and patient oriented research, as part of the Second International ALS Conference in Tarrytown, NY, USA, seven pairs of clinicians and scientists were asked to lead discussions with meeting attendees on six major topics (one of which was discussed by two groups); each one the focus of a 90-min Breakout Session. Approximately 25 meeting attendees participated in each session. The Breakout Sessions considered six major themes: 1) Approaches to encourage clinicians to engage in more clinical research to discover the pathogenesis and cause of ALS; 2) Exploring avenues to build more effective partnerships between basic scientists and ALS physicians; 3) Increasing patient interest and commitment to participating in non-trial clinical research; 4) Brainstorming about factors that are most critical to the discovery of the pathogenesis and cause of ALS; 5) Finding ways to incorporate clinical research projects into clinical trials; and 6) Developing state-of-the-art epidemiological studies to solve the mystery of ALS. In this paper, we present the reports from each of the Breakout Sessions; and we provide a wrap-up of the entire conference.